2014
DOI: 10.1063/1.4874176
|View full text |Cite
|
Sign up to set email alerts
|

Metacomposite characteristics and their influential factors of polymer composites containing orthogonal ferromagnetic microwire arrays

Abstract: The microwave properties of glass-fibers reinforced polymer composite embedded with an orthogonal array of Fe 77 Si 10 B 10 C 3 microwires have been investigated. The composites containing orthogonal wire arrays display a remarkable transmission window in the frequency band of 1 to 6GHz under zero external magnetic field indicating an intrinsic double-negative-index characteristic.The polymer matrices have proved to exert a synergistic effect on the microwave properties, which is responsible for the disappeara… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Based on this perspective, fruitful experimental results and their underlying physics pertinent to ferromagnetic microwire composites have been systematically studied associated with other influential roles at play, for instance, the wire volume fraction [10], wire length [11] and polymer matrices [12]. From all these exciting studies, microwire composites are believed to be used in potential applications such as microwave devices and sensors in the future.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Based on this perspective, fruitful experimental results and their underlying physics pertinent to ferromagnetic microwire composites have been systematically studied associated with other influential roles at play, for instance, the wire volume fraction [10], wire length [11] and polymer matrices [12]. From all these exciting studies, microwire composites are believed to be used in potential applications such as microwave devices and sensors in the future.…”
Section: Introductionmentioning
confidence: 98%
“…Based on this perspective, fruitful experimental results and their underlying physics pertinent to ferromagnetic microwire composites have been systematically studied associated with other influential roles at play, for instance, the wire volume fraction, 7 wire length 8 and polymer matrices. 9 From all these exciting studies, this nascent research area is confirmed to have great scientific value and microwire composites are believed to be used in potential applications such as microwave devices and sensors in the future. It is therefore of significant interest to dispose a panorama on the microwire composites to summarize the on-going research on their fabrication, characterization and perspective application from the standpoint of engineering.…”
Section: Introductionmentioning
confidence: 99%
“…Glass coated amorphous microwires have been intensively studied due to its outstanding magnetic properties, as giant magnetoimpedance (GMI) [1][2][3][4][5][6][7][8][9] or its absorption properties at microwave frequencies [10][11][12][13][14][15][16][17][18][19]. The GMI effect is related to the change of the skin depth on the microwire due to strong changes of the dynamic circular permeability [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…As discussed in previous work, the orthogonal microwire array can generate DNG features in the microwire-polymer system due to the significantly improved fp arisen from the additional dielectric contribution provided by the vertical wires. 29 However, it remains an issue to tune the identified transmission windows in such orthogonal structure. With reference to Fig.…”
Section: "mentioning
confidence: 99%
“…This small deviation can be attributed to the non-uniform distribution of frozen-in stresses during the fabrication of the microwires, 32,38 as well as the residual stress distribution at the microwire/polymer interface. 29 Co-based microwires have a much smaller NFMR frequency compared to Febased ones, but the position of the resonance peak can be effectively tuned by the external magnetic bias. 13,15 However, the fact that the position of transmission window is not affected by the presence of external fields implies that the left-hand behavior is independent of the intrinsic properties of Co-based microwires at the low frequencies regime (Fig.…”
mentioning
confidence: 99%